Regulatory Developments in the U.S. : History and Philosophy - Thompson, Louis S. (World Bank, Washington, DC, 2014)
The first nationwide regulation of transportation in the United States (U.S.) was intervention in railways. In the 1830 to 1880 period, railways had been over-built in many areas of the country especially the Northeast mainly because of financial speculation in the creation of railway companies. The perceived "high fixed cost, low variable cost" structure of railways tended to generate severe rate cutting and tariff instability whenever railways directly competed for traffic. Another major thrust was "locational" (regional) interests - farmers who wanted rates averaged and stabilized so that more distant markets will see the same transport costs as the "more fortunate", closer farms, and so that ports can be "equalized". This report gives the growth of transport regulation in the U.S.; results of regulation; why was regulatory change necessary at the beginning of the 1980's?; and the deregulatory experience in the U.S.